Pendekatan Intrinsik pada Syair Umru al-Qais Menyingkap Visi Kemanusiaan Zaman Pra-Islam - Abdullah Abdullah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
One of the proper view in literary critical world is independentliterary work. This ideology views literary work must show the formation of element linkage that act the role and function totally Epistemologically.it shows the popular approach, that is intrinsic. which determines the independent structur that can be studied as unity with its develop element This approach contains three main ideas, they are global structural transformation, and independent idea. Therefore, understanding literary work means establishing element structure. This approach reconstructs the linkage of the literary elemet with its main basic such as text, structure, and transformation.